2021
DOI: 10.1108/ijbpa-06-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the robotics implementation barriers for construction projects in developing countries

Abstract: PurposeThe purpose of this paper is to evaluate the barriers militating against the adoption of robotics in the construction industry.Design/methodology/approachRobotics implementation barriers were obtained from the previous studies and then through questionnaire survey construction stakeholders in Nigeria evaluate these barriers. Consequently, these barriers were examined via the exploratory factor analysis (EFA) technique. Furthermore, a model of these barriers was implemented by means of a partial least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 101 publications
2
16
0
Order By: Relevance
“…The findings revealed that deployment of R&A for safer construction worksites in South Africa is impeded by four major groups of industry, technology, human and costrelated factors. These grouped factors are consistent with existing literature that have grouped the barriers to the use of R&A and related technologies in both developed and developing countries worldwide (Delgado et al, 2019;Huang et al, 2021;Oke et al, 2021;Trujillo and Holt, 2020). However, while Oke et al (2021) submitted that cost and technologyrelated issues are the major barriers to the use of robotics in the construction industry in Nigeria, this current study found that the barriers exceed these two groups to include industry and human-related factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings revealed that deployment of R&A for safer construction worksites in South Africa is impeded by four major groups of industry, technology, human and costrelated factors. These grouped factors are consistent with existing literature that have grouped the barriers to the use of R&A and related technologies in both developed and developing countries worldwide (Delgado et al, 2019;Huang et al, 2021;Oke et al, 2021;Trujillo and Holt, 2020). However, while Oke et al (2021) submitted that cost and technologyrelated issues are the major barriers to the use of robotics in the construction industry in Nigeria, this current study found that the barriers exceed these two groups to include industry and human-related factors.…”
Section: Discussionsupporting
confidence: 90%
“…These grouped factors are consistent with existing literature that have grouped the barriers to the use of R&A and related technologies in both developed and developing countries worldwide (Delgado et al, 2019;Huang et al, 2021;Oke et al, 2021;Trujillo and Holt, 2020). However, while Oke et al (2021) submitted that cost and technologyrelated issues are the major barriers to the use of robotics in the construction industry in Nigeria, this current study found that the barriers exceed these two groups to include industry and human-related factors. More so, it was discovered that only the industry, human and cost factors would significantly affect the attainment of better H&S, improved productivity, competitive advantage and overall project success delivered through improved H&S, as seen in Figure 3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, using semi-structured interviews, Pan et al (2020a, 2020b) identified the key factors that will influence the technological transformation of construction holistically by analysing the interactions between factors that will impact the future use of construction robots, whereas Oke and Kineber (2021) used a questionnaire survey to model the robotics implementation barriers for construction projects in developing countries. Bogue (2018) examined the present uses and potential future roles of robots in the construction industry through a literature review assessment approach, an approach also adopted by Mcmeel (2019) on an analysis of how new technology is implemented and combined in robots and augmented reality.…”
Section: Results and Analysismentioning
confidence: 99%
“…Respondents reported robotics drivers and adoption benefits on an experience and knowledge basis utilizing a five-point Likert scale, with scores of 5 and 1 representing very high and very low, respectively, with high, average, and low scores falling between 5 and 1. This scoring system has been broadly applied in many studies, including those concerned with construction management [84][85][86][87][88][89][90]. The study was designed to provide stakeholders with a variety of solutions based on practice in a range of construction schemes.…”
Section: Methodsmentioning
confidence: 99%